FERTILITY IN CONGENITAL ADRENAL HYPERPLASIA: A CASE REPORT - Hashim, Uswaton Hasanah; Abas, Syarifah Syahirah Syed; Karim, Nor Afidah; Sin, Yong Lit; Adam, Noor Lita (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Congenital adrenal hyperplasia (CAH), an autosomal recessive disorder affecting cortisol biosynthesis enzymes, results in virilization in affected females. Fertility challenges are often faced by females with CAH. We present two women with CAH who achieved successful spontaneous pregnancy and their pregnancy outcomes. CASE 1 Ms. NAS, a 28-year-old Malay female, was diagnosed with 21-hydroxylase deficiency (21-OHD) at birth (presentation: ambiguous genitalia) and underwent corrective surgery at one year of age. She attained menarche at the age of 12 before having secondary amenorrhea for one year at 13 years old. She had normal menstrual cycles while on hydrocortisone 10 mg BD. Pre-pregnancy investigations were as follows FSH 4.04 IU/L, LH 2.22 IU/L, testosterone 2.22 nmol/L, dehydroepiandrosterone Sulphate (DHEA-S) 1.040 umol/L (NR 2.68-9.23). She safely delivered her baby via spontaneous vaginal delivery. CASE 2 Ms. NN, a 22-year-old female, was diagnosed with CAH at 1 month of life presenting with a salt-losing crisis. She developed precocious puberty at 9 years old due to poor compliance to treatment. She was on triptorelin (Decapeptyl) sc for 2 years until the age of 12. She successfully conceived at the age of 21. Pre-pregnancy, she was treated with T hydrocortisone 5 mg/5 mg/7.5 mg TDS and T fludrocortisone 0.1 mg OD. Her hormonal level preconception were as follows: testosterone <0.1 nmol/L, 17 hydroxyprogesterone (17 OHP) 71.9 nmol/L (elevated), DHEA-S 0.349 umol/L (suppressed). Her pregnancy was uneventful, and successfully delivered her baby surgically after having transverse lie at term. The differences between the 2 cases (presentation of CAH, the need for genital reconstructive surgery, the nature of puberty) did not impair the fertility potential of these 2 patients during adulthood. CONCLUSION Management of CAH during pregnancy is important to ensure successful term delivery with no added pregnancy complications like gestational diabetes or hypertension.